Reproductive health service utilization and associated factors among secondary school students in Harari regional state, eastern Ethiopia, 2022: a multicenter study - Addisu Sertsu; Addis Eyeberu; Tilahun Bete; Elias Yadeta; Magarsa Lami; Tegenu Balcha; Bekelu Berhanu; Ayichew Alemu; Fentahun Meseret; Hanan Mohammed; Addisu Alemu; Ahmed Mohammed Husen; et al. (BMC, 2023)
Abstract Introduction Reproductive health encompasses all conditions relating to the reproductive system and goes beyond simply being free from disease or infirmity. Several socioeconomic and socio-cultural factors affect reproductive health service utilization. Objectives To assess reproductive health service utilization and its associated factors among government secondary school students in Harari regional state, Eastern Ethiopia 2022. Methods A school-based cross-sectional study design was conducted among 1275 secondary school students in six randomly selected secondary schools in Harari Regional state, in eastern Ethiopia. The study participants were chosen using a simple random sampling method. Data was gathered using self-administered questionnaires, entered into Epi Data version 3.1, and exported to SPSS version 25 for cleaning and analysis. Descriptive statistics, bivariable, and multivariable logistic regression analyses were carried out to compute the frequency of each independent variable and the magnitude of the outcome variables, then to identify factors associated with the outcome variable, respectively. To declare a significant association, an adjusted odd ratio (AOR) with a 95% confidence interval and a p-value of 0.05 were used. Results Our finding indicated that 25.3% (95% CI:22.9, 27.7) of the secondary school students utilized reproductive health services. Being in grade 11-12 (AOR = 1.67, 95% CI: 1.18, 2.38), having a history of sexually transmitted infection (AOR = 6.11, 95% CI: 2.20, 16.99), presence of a health facility nearby (AOR = 1.49, 95% CI: 1.12, 1.99), discuss voluntary counseling and testing with family (AOR = 2.73, 95% CI: 1.90, 3.94), and discussing about contraceptive with friends (AOR = 1.22, 95% CI: 0.91, 1.65) were the elements that had a strong correlation with reproductive health service utilization. Conclusion In this study, only one-fourth of secondary school students utilized RH service during the past year. The student's educational level, having a history of STI, the presence of a health facility nearby, and discussing RH service with family/friends were the factors significantly associated with reproductive service utilization among secondary school students.